Augustus And “The Augustan” In Spanish Archaeology: A Historiographical Revision During The 19th And 20th - Beltrán Fortes, José (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
An analysis of Spanish archaeological and antiquary activities and publications during the 19th and 20th centuries leads to the conclusion that no special treatment was given to the public figure of Augustus by Spanish archaeology. Despite the fact that the Roman Hispania was organized in the Augustan period and lasted many centuries, Spanish historiography emphasises other periods and public personalities, such as Caesar and Trajan. Instead discussion was of the Augustan period, and not until the last quarter of the 20th century was there greater interest for the period of the Principate, in relation with the development of classical archaeology in Spain and under the influence of outside processes.